The Influence of Brand Image and Lifestyle on Iphone Purchasing Decisions in Cirebon City - Nauval Ramadhan; Hary Siswanto; Soesanty Maulany (Rescollacom (Research Collaborations Community), 2025)
The development of lifestyle trends and increasingly strong brand images in Indonesia have a major influence on consumer purchasing decisions, especially in the technology product category such as the iPhone. This creates very tight competition in the gadget market. This study aims to analyze the influence of lifestyle and brand image on purchasing decisions for iPhone products, especially for consumers in Indonesia. Product purchasing decisions will be influenced by lifestyle factors and brand image owned by consumers. In this study, primary data were collected using a Likert scale questionnaire. The questionnaire was systematically designed to collect responses relevant to the research topic and consisted of a series of questions distributed to respondents aged 18 to 35 years, with a calculation of the coachran formula for 380 respondents. The data analysis method was carried out using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of the study showed that lifestyle and brand image had a significant influence on purchasing decisions for iPhone products. This means that these two independent variables together drive iPhone purchasing decisions, with lifestyle and brand image playing an important role in shaping consumers' desire to buy the product. A modern lifestyle and a positive brand image are the main factors driving iPhone purchasing decisions. This shows that consumers choose products based on social identity and brand quality that can meet their lifestyle needs.